A rapid review of best practices in the development of risk registers for public health emergency management - Kostirko, Danylo; Zhao, Jiawei; Lavigne, Melissa; Hermant, Benoit; Totten, Liam (Frontiers in Public Health, 2023)
Public health organizations (PHO) must prepare to respond to a range of emergencies. This represents an ongoing challenge in an increasingly connected world, where the scope, complexity, and diversity of public health threats (PHT) have expanded, as exemplified by the COVID-19 pandemic. Risk registers (RR) offer a framework for identifying and managing threats, which can be employed by PHOs to better identify and characterize health threats. The aim of this review is to establish best practices (BP) for the development of RRs within Public Health Emergency Management (PHEM).